Internet censorship detected in Tanzania (Tanzania) - Voidly (2026)
CRITICAL severity censorship detected in Tanzania. Confidence: 65%. Data sourced from CensoredPlanet.
Censorship Incident ID: TZ-2026-0017
Keywords: censorship; TZ; censorship; critical